A ascensão dos pobres a posições de elite político-administrativa no contexto do Cabo Verde pós-independente - Crisanto Barros (Ciências Sociais Unisinos)
The administration of the modern Cape Verdean State, which results from profound changes instituted during the second half of the nineteenth century, is made largely by natives of the archipelago, whose recruitment was done predominantly within the most favored families. This tendency still prevails throughout the twentieth century, despite having suffered a slight change in the late sixties. This article aims to analyze the rise of grassroots individuals to the political and administrative elite with the institutionalization of the National State from 1975 onwards. In the scope of this essay, we will focus our analysis on the trajectories of the political and administrative elite coming from the most disadvantaged social strata of the Cape Verdean society. Our goal is to understand the historical conditions and individual and family strategies which contributed to make their presence more frequent during the last quarter of the twentieth century.